126 Is heart failure admission over weekends and bank holidays associated with higher risk of death?. (4th June 2021) - Awad, Reham; Joseph, Prince; Owen, Emily; Khan, Shamshad; Hilal-Babu, Mohammed; Avinash, Sunita; Masudi, Sundas; Bahar, Jameela; Bennett, Haydn; Wong, Kenneth; Rahman, Amna
Abstract : Introduction: - Acute Heart failure inpatient mortality is as high as 7-11% in UK National Heart Failure audits with little improvement over many years. Some but not all studies have suggested a possible weekend effect on mortality in different patient groups including patients suffering from heart failure. However, some studies failed to recognise admissions after 5pm on Fridays as weekend. We aim to determine in a large cohort of heart failure admissions whether patients are less likely to survive if admitted during weekend or Bank Holidays. Methods: - A retrospective study of consecutive admissions with heart failure as 1st diagnostic position in Blackpool Victoria Hospital over an 18 month period from 1st August 2019 to 31st January 2021. Normal working hours is defined as 9am to 5pm during weekdays except UK Bank holidays. Results: - Of 1178 episodes of heart failure admission, there were 140 inpatient deaths (11.9%). Median age at admission was 80 [interquartile range 70, 86]. 48 (4.1%) were COVID positive, 34% negative. 60.4% were not tested. 405 patients were admitted over the weekend/bank holiday (34.4%) . The other 773 patients (65.6%) were admitted during normal working hours (9am to 5pm during weekdays). The length of stay is not significantly different whether patients are admitted over weekend /bank holidays or during normal working hours median 11 days [5, 19] vs 11 days [5, 21] admitted during normal working hours, p=0.48. Inpatient mortality in patients admitted with heart failure over the weekend/bank holiday was 1.3 times higher, but this apparent increased risk was not statistically significant (95% confidence interval of the odds ratio=0.98-1.8, Fisher exact 2-tailed p= 0.2). Conclusion: There is no significant difference in inpatient mortality between patients admitted with heart failure during normal working hours or during weekends and bank holidays. Future research will explore reasons (including the use of evidence based drugs, timely diagnosis with echocardiography and the impact of COVID). Conflict of Interest: Heart Failure